Antibacterial Activity Test Of Ethanolic Extract Patch Preparations From Noni Leaves (Morinda Citrifolia L.) Using The Zone Of Inhibition Against Staphylococcus Aureus And Staphylococcus Epidermidis Bacteria - Yanti Musyaawarah; Suharyanisa Suharyanisa; Jon Kenedy Marpaung; Aditiya Baginda Marpaung (Journal of Innovative and Creativity, 2025)
Wounds occur when there is damage or loss of body tissue due to factors that interfere with the body's protective system and cause infection caused by Staphylococcus aureus and Staphylococcus epidermidis.Noni leaf (Morinda citrifolia L.) has strong potential as an antibacterial, so researchers are interested in formulating ethanol extract of noni leaf (EEDM) into a patch preparation. Objective: Knowing that EEDM can be formulated as a patch preparation, as well as knowing its antibacterial activity. Methods: Four formulas were made with variations in extract concentration, namely F0 (blank); FI : 5%; FII: 10%; and FIII: 15%. Antibacterial testing using disc paper diffusion method. Results: A clear patch preparation was produced in F0, while in FI, FII and FIII the gel was blackish green with a distinctive smell of EEDM. The results of the antibacterial activity test against Staphylococcus aureus in each formula are FI: 2.58 mm; FII: 2.35 mm; FIII: 2.41 mm, while against Staphylococcus epidermidis, FI: 1.46; FII: 2.28; FIII: 3.33. Conclusion: EEDM can be formulated into patch preparations. The antibacterial potential of the three formulas is in the weak category.